Penataan Kawasan Wisata Pantai Batu Cincin Di Kabupaten Ende - Mariam, Siti; Siso, Silvester M.; Dede, Petrus Jhon Alfred Depa (TEKNOSIAR, 2022)
One of the beaches that has good natural potential and has been recognized by the Department ofCulture and Tourism of Ende Regency is Stone Ring Beach which is located in Ende Regency. StoneRing Beach is located in Raporendu Village, Nangapanda District, Ende Regency. The stone ringbeach itself is a cliff that is at sea level and there are holes like stone rings that are unique on thebeach. There is no road as vehicle access to enter Stone Ring beach because the area is still natural.The research with the title "Arrangement of Stone Ring Beach Tourism Area in Ende Regency" has aproblem formulation of how to organize Stone Ring Beach with facilities or infrastructure in order tosupport the activities of visitors. The purpose of this research is to plan and design the main facilitiesand supporting facilities that can make Stone Ring Beach an attractive and superior touristdestination.In this study, qualitative and quantitative research methods were used, while the data sourcesused were obtained from the results of direct observations and interviews with the community, villageofficials, and visitors to Stone Ring Beach. The data obtained will then be analyzed, the analysis usedincludes drafting site processing concepts, compiling zoning and utility concepts, compiling conceptsfor relations, magnitude, and space requirements, compiling concepts for spatial planning andcirculation, drafting regional characteristics concepts, drafting structural and construction concepts.The concept of formation that will be planned is to use the roof of the traditional house of Endedistrict and the surrounding community by considering the concept of ecotourism in order to maintainthe culture around the area.Based on the data analysis that has been carried out, the results obtainedfrom the analysis of the design of the Stone Ring beach tourist area refer to the concept of EcotourismArchitecture which is expected to develop the Stone Ring beach tourist area which has main facilitiesand adequate supporting facilities and can attract tourists to come and visit. The application of theEcotourism Architecture theme is also expected to improve the community's economy and not damagethe surrounding environment.